IMPLIKASI HUKUM TATA NEGARA TERHADAP PENGATURAN MEDIA SOSIAL DI ERA DIGITAL: PERSPEKTIF KEBEBASAN BERPENDAPAT - Darussalam, Mohammad (PRODI HUKUM TATANEGARA, 2024)
In the increasingly developing digital era, social media has become the main platform for communication and interaction between citizens. The presence of social media, which includes various platforms such as Facebook, Twitter, Instagram, and TikTok, not only facilitates information sharing, but also creates a space for individuals to express opinions and participate in public discussions. However, this phenomenon brings significant challenges to constitutional law, especially in the context of freedom of expression. This journal examines the implications of constitutional law for the regulation of social media, highlighting how the regulations implemented can affect individuals' rights to express opinions. This research uses a qualitative approach with analysis of relevant regulations as well as case studies from various countries facing similar situations. The research results show that although the state has the right to regulate social media in the public interest, these regulations must be balanced and not curb freedom of expression.